Liability in Software License Agreements. - Warme, David (Communications of the ACM, 2015)
The article presents a letter to the editor concerning the column “‘But Officer, I was Only Programming at 100 Lines Per Hour!," which discusses liability for software developers, by Vinton G. Cerf in the July 2013 issue.